Hardness enhancement of Al-Si alloys from sand casting with runner variations - Tsamroh, Dewi Izzatus; Ardiansyah, Mochammad Fachrizal; Yaqin, Mohammad Ainul; Shiddiqy, Taqiyyudin Ahmad As; Lubis, Didin Zakariya (JURNAL MECHANICAL, 2024)
Metal casting is one of the oldest and most efficient manufacturing techniques in producing metal components with complex shapes. One of the main challenges in the casting process is controlling the flow of molten metal so that it can fill the mold perfectly without producing defects. The channel in the casting mold is usually called a runner. The runner functions as a distribution channel for molten metal into the mold cavity. Optimal runner design settings are very important to prevent defects in the final product such as porosity, cold shut, and shrinkage. This study aims to identify the effect of runner shape variations on the quality of Al-Si casting. The method used in this study is a laboratory experimental method. The study began with preparing the tools and materials, the materials used in this study were used pistons. The piston melting temperature was carried out at 750°C. The results showed that the results of the cast product using a truncated cone-shaped runner (variation 1) were the best results. Macrostructural analysis showed that specimens in variation 1 had minimum casting defects and lower shrinkage compared to variation 2. Microstructural analysis showed that the cast product produced several phases. Meanwhile, the hardness number for specimen variation 1 reached 98 HRE.